Factors Influencing the Growing Demand of Cardless ATM Cash Withdrawal - Shrestha, Sajeeb Kumar; Singh, Ayushi; Mahat, Dipak; Neupane, Dasarath; Karki, Tej Bahadur (People’s Journal of Management, 2025)
This study investigates the factors influencing the rising adoption of cardless ATM cash withdrawals in Nepal, focusing on perceived ease of use, customer trust, perceived usefulness, perceived security, and amount of information. Using a mixed-method approach with 107 respondents, data were analyzed via SPSS, revealing that perceived security and amount of information significantly drive demand, while traditional factors like ease of use and trust showed weaker impacts. These insights challenge conventional assumptions and offer actionable strategies for financial institutions to enhance user adoption through targeted security measures and educational campaigns.